2014
DOI: 10.1007/s13277-014-1992-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin in tumor hypoxia: novel insights into cancer suppression

Abstract: Emerging new and intriguing roles of cytoglobin (Cygb) have attracted considerable attention of cancer researchers in recent years. Hypoxic upregulation of Cygb as well as its altered expression in various human cancers suggest another possible role of this newly discovered globin in tumor cell response under low oxygen tension. Since tumor hypoxia is strongly associated with malignant progression of disease and poor treatment response, it constitutes an area of paramount importance for rational design of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 104 publications
0
22
0
1
Order By: Relevance
“…Cytoglobin is able to bind oxygen, and it is known to regulate oxygen levels in cancer cells during hypoxia [19]. Cytoglobin is a stress-related gene, and its expression level is upregulated during oxidative stress in tumors [19]. Our data has shown that the level of cytoglobin is increased many folds in NSCLC cells and tumor xenografts ( Figure 2 C and 2D).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Cytoglobin is able to bind oxygen, and it is known to regulate oxygen levels in cancer cells during hypoxia [19]. Cytoglobin is a stress-related gene, and its expression level is upregulated during oxidative stress in tumors [19]. Our data has shown that the level of cytoglobin is increased many folds in NSCLC cells and tumor xenografts ( Figure 2 C and 2D).…”
Section: Discussionmentioning
confidence: 71%
“…In cancer cells and tumor xenografts, an increase in heme synthesis and uptake occurs concomitantly with increased levels of hemoproteins such as cytoglobin ( Figure 2C), cytochrome c, Cox-2 and CYP1B1. Cytoglobin is able to bind oxygen, and it is known to regulate oxygen levels in cancer cells during hypoxia [19]. Cytoglobin is a stress-related gene, and its expression level is upregulated during oxidative stress in tumors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia induces Cygb upregulation and protects cancer cells from ONS-induced apoptosis. [23][24][25][26] Thus the anti-tumor effect and underlying mechanism of Cygb need to be further explored.…”
Section: The Interaction Of Ons Withmentioning
confidence: 99%
“…Interestingly, Cygb appears to confer intriguing protective properties in tumor cell against oxidative stress injury. Hypoxia induces Cygb upregulation and protects cancer cells from ONS‐induced apoptosis . Thus the anti‐tumor effect and underlying mechanism of Cygb need to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is a double-edged-sword as Cygb appears to function not only as a tumor suppressor but also protects hypoxic tumors against therapy. The potential role of Cygb in cancer suppression and hypoxic tumor protection has been recently reviewed (15).…”
Section: Neuroglobin and Neuroprotectionmentioning
confidence: 99%